Practices of Preceptor Nurses on Protective, Socialisation, and Role Model Roles - Hatice Çamveren; Havva Arslan Yurumezoglu; Ebru Melek Benligül; Gülseren Kocaman (Association of Nurse Managers, 2021)
Aim: This study aimed to investigate preceptor nurses' practices regarding their 'protective socialisation and role model' roles. Method: This study was conducted with 135 preceptor nurses in a university hospital between March and June 2018. Preceptor nurses were asked an open-ended question on their practices regarding protective, socialisation, and role model roles. Their answers were analysed with content analysis. Results: The participating nurses' mean age was 33.99+-3.54. Of them, 94.1% previously worked as a preceptor nurse for at least one year. While supporting new nurses, taking measures to reduce the error risk and defending them against other team members are preceptor nurses' protective roles. Helping new nurses adapt to the team and the clinical environment is their socialisation role. Furthermore, displaying professional behaviours and establishing appropriate communication are their role model roles. Conclusion: Preceptor nurses fulfil their roles by supporting new nurses, making them feel like they belong to the team, and establishing appropriate communication. The results of this study may guide manager nurses to create working environments contributing to preceptor-new nurse harmony and develop preceptorship programs to meet new nurses' needs.